Analysis of the Direct Instruction Model in Mathematics Learning on Number Factors Material in Grade 4A at SDN Mertasinga 06 Cilacap for the 2024/2025 Academic Year - Susy Abidin; Kuntoro Kuntoro (UM Purwokerto Press, 2025)
This study was conducted in the fourth grade of SDN Mertasinga 06 Cilacap using the direct instruction model in the Mathematics subject on number factors. It can be concluded that the use of the direct instruction model in Mathematics learning can improve students' learning outcomes. Students showed enthusiasm when lessons were delivered directly, especially when combined with engaging games. Data were collected by the teacher through interviews, direct observation during the learning process, and document analysis in the form of students' learning results. The study findings indicate that the implementation of the direct instruction model enhances students' learning outcomes, particularly in terms of understanding the lesson material and communication skills. Through activities such as reading, answering questions, discussing, and explaining, students were more actively involved in the learning process, which ultimately led to improved learning outcomes. Additionally, the direct instruction model increased students' learning motivation, making them more interested and excited about every learning activity. Based on these findings, it is recommended that the direct instruction model be more widely implemented in elementary schools to enhance the effectiveness and quality of learning.